Urinalysis and body fluids - Strasinger, Susan King; Di Lorenzo, Marjorie Schaub (Philadelphia, Pennsylvania : F. A. Davis Company, 2014)
Here's a concise, comprehensive, and carefully structured introduction to the analysis of non-blood body fluids. Through six editions, the authors, noted educators and clinicians, have taught generations of students the theoretical and practical knowledge every clinical laboratory scientist needs to handle and analyze non-blood body fluids, and to keep themselves and their laboratories safe from infectious agents. Their practical, focused, and reader friendly approach first presents the foundational concepts of renal function and urinalysis. Then, step by step, they focus on the examination of urine, cerebrospinal fluid, semen, synovial fluid, serous fluid, amniotic fluid, feces, and vaginal secretions. The 6th Edition has been completely updated to include all of the new information and new testing procedures that are important in this rapidly changing field. Case studies, clinical situations, learning objectives, key terms, summary boxes, and study questions show how work in the classroom translates to work in the lab.
Safety and quality assessment -- Introduction to urinalysis -- Renal function -- Physical examination of urine -- Chemical examination of urine -- Microscopic examination of urine -- Renal disease -- Urine screening for metabolic disorders -- Cerebrospinal fluid -- Semen -- Synovial fluid -- Serous fluid -- Amniotic fluid -- Fecal analysis -- Vaginal secretions.
Includes bibliographical references and index.
Keywords: URINE -- ANALYSIS